직접 및 간접 디지털 인상을 병용한 임시 의치 제작 증례 - 박지수(Ji-Su Park); 이청희(Cheong-Hee Lee); 이규복(Kyu-Bok Lee); 이두형(Du-Hyeong Lee); 유현지(Hyun-Ji Yu); 김소연(So-Yeun Kim) (Journal of dental rehabilitation and applied science, 2024)
Through the use of intraoral scanners, it is possible to obtain intraoral scan impressions and produce prostheses. This approach is also being attempted not only in dentate patients but also in edentulous patients. However, obtaining scans of edentulous areas can be more challenging than scanning dental areas, and there may be limitations, especially in capturing the details of the mucosal tissues. On the other hand, when obtaining impressions with intraoral scanners, simultaneous recording of the occlusal relationship of the maxilla and mandible can reduce the number of patient visits and expedite the restoration process. In this case, we aimed to combine the advantages of direct intraoral scanning and indirect digital impressions obtained after traditional impression-taking by merging two types of scan files. Consequently, in patients with partially edentulous arches, we sought to provide effective interim prostheses through direct and indirect digital model impressions and report our findings accordingly. 구강 스캐너를 통해 구내 스캔 인상을 획득하여 보철물을 만들 수 있으며 이는 유치악 뿐 아니라 무치악 환자에서도 시도되고 있다. 그러나 무치악 부위는 치아 부위보다도 인상채득이 까다로우며 특히 변연부의 인상채득은 스캔의 한계가 있다. 한편 구강 스캐너를 통한 인상채득 시에는 상하악의 인상채득과 동시에 악간관계를 동시에 채득하여 환자의 내원 횟수를 줄일 수 있어 저작의 회복을 더 빠른 시일 내에 이룰 수 있다는 장점이 있다. 이에 본 증례에서는 구강 내의 직접스캔과 전통적 인상채득 후 얻은 모형의 간접 디지털 인상을 이어서 중합하는 방식으로 양측의 장점을 얻고자 하였다. 결과적으로 부분 무치악으로 저작을 상실한 환자에게 직간접 디지털 모형 인상채득을 통해 효과적으로 임시의치를 제공하여 이를 보고하고자 한다.